THE APPRAISAL SYSTEM OF HYPERBOLIC EXPRESSIONS IN SETIYONO'S 'GLONGGONG' NOVEL TRILOGY - Rahmaditya Khadifa Abdul Rozzaq Wijaya; Aris Hidayatulloh (UIN Raden Mas Said Surakarta, 2022)
This study aimed to find out the appraisal system in the hyperbolic figure of speech. is a qualitative-descriptive study with data in the forms of words, phrases, and clauses indicating hyperbolic figurative language and having appraisal systems. The sources of data were the novel trilogy entitled Glonggong that consists of Glonggong, Arumdalu, and Dasamuka. For collecting the data, focus group discussion and content analysis were applied, whereas for analyzing the data, it used Spradley’s Ethnography Method comprising domain, taxonomy, componential, and cultural theme analysis consecutively. The result of this study show that hyperboles as a type of figurative language in the narratives and dialogues of the novel have appraisal systems in the forms of attitude, graduation, and source.